The Imaginative in the Service of the Rational - Jude Godwins (ESUT JOURNAL OF SOCIAL SCIENCES, 2024)
Until most recently this intellectual climate remained, as it were, sacrosanct. It was an academic and theoretical climate where there could be only one conceptual system and only one accurate way of understanding the world. In our day developments in the cognitive sciences occasion a battery of agitating questions. To what extent are reason and thought mere manipulation of abstract symbols? Are they actually only about the correspondence of words and mental representations to the external world, independently of the nature and body of the human being involved in the operation? Are the symbols used in thought actually meaningless, only getting their meaning by corresponding to things in the physical world? Are reason and concepts really transcendental, in the sense of not being liable to the natures and bodies of the thinking beings? To what extent does the human mind mirror reality as it is “out there”? Is nature really mirrored in our mathematical reasoning? Are our concepts in truth internal representations of external realities? Are thought and reason not instead a matter of the nature of the thinking being -  its body, social character, environmental interactions? The foregoing questions, as it were, boil down to the problem of the kind of beings that we are, with the kind of bodies that we have. This natural given (or disposition) gives rise to our use of our imaginative faculties and processes. And these have consequences.